Modern Vintage Homes & Leisure Lives Ghosts & Glamour - Holland, Samantha (Leisure Studies in a Global Era, 2018)
This book explores the meanings and practices of vintage lives. It focuses on the non-mainstream subculture of vintage clothes and lifestyle, specifically that of the 1940s, 1950s and 1960s, and asks how those engaged in the culture place themselves within the gendered and classed contexts of these eras. As a result, it also identifies the tensions involved in these identities connected to a past that offered little gain for women and narrow gender roles for both women and men. Modern Vintage Homes & Leisure Lives is based on original empirical international data about a group of people who wear vintage clothing all of the time and whose homes are styled entirely, or almost entirely, vintage. It aims to understand the meanings of vintage for them through their daily practices and accrued knowledge. Through interviews and direct observations of vintage events it also explores questions about the acquisition, display and curation of vintage clothes, homes and objects, about glamour and wardrobes, about the history of second-hand markets, and emotional durability and ideas about ghosts, hauntings and spectral remains. It will be of particular interest to students and academics of gender and women's studies, fashion and design, fashion history, cultural studies, the body and embodiment.